Association of Sickle Cell Disease With Severe Maternal Morbidity. Issue 1 (30th January 2023) - Ha, Thoa K.; Boulet, Sheree L.; Cotsonis, George; Geary, Franklyn; Jamieson, Denise J.; Lindsay, Michael
Abstract : Delivering individuals with sickle cell disease had a fivefold increased risk of severe maternal morbidity. Abstract : OBJECTIVE: To evaluate the association between sickle cell disease (SCD) and severe maternal morbidity (SMM) in a contemporary cohort of deliveries by non-Hispanic Black people. METHODS: We retrospectively examined SMM by using electronic health record data on deliveries by non-Hispanic Black patients between 2011 and 2020 at a single tertiary, public institution. Sickle cell disease was identified during the delivery admission by using International Classification of Diseases, Ninth Revision, Clinical Modification (ICD-9-CM) and International Classification of Diseases, Tenth Revision, Clinical Modification (ICD-10-CM) codes. The primary outcome, SMM at delivery hospitalization, was ascertained using ICD-9-CM and ICD-10-CM codes and excluded sickle cell crisis as an indicator of SMM. We also constructed a secondary measure of SMM that excluded deliveries in which blood transfusion was the only indication of SMM. Poisson regression models were used to estimate risk ratios (RRs) and 95% CIs for the associations between SCD and SMM (overall and for individual indicators). Multivariable models adjusted for age, parity, insurance type, chronic conditions (chronic hypertension, diabetes mellitus, obesity), and multiple gestation. RESULTS: Among 17, 493 deliveries by non-Hispanic Black patients during the study period, 132 (0.8%) had a diagnosis of SCD. Of those patients, 87 (65.9%, 95% CI 57.2–73.9) with SCD and 2, 035 (11.7%), 95% CI 11.2–12.2) without SCD had SMM. Sickle cell disease was associated with increased risk of SMM (87 vs 2, 035, adjusted risk ratio [aRR] 5.4, 95% CI 4.6–6.3) and nontransfusion SMM (51 vs 1, 057, aRR 6.0, 95% CI 4.6–8.0). Effect estimates were highest for cardiac arrest (3 vs 14, RR 28.2, 95% CI 3.8–209.3), air and thrombotic embolism (14 vs 72, RR 25.6, 95% CI 12.0–54.6), and puerperal cerebrovascular disorders (10 vs 53, RR 24.8, 95% CI 10.2–60.5). CONCLUSION: Sickle cell disease was associated with a more than fivefold increased risk of SMM during the delivery hospitalization. Our data suggest cardiovascular morbidity as the driving major risk. The identification and monitoring of cardiovascular pathology in patients with SCD before and during pregnancy may reduce SMM.